Exemplary Projects in House Building of the 1730s–1760s in St. Petersburg: Problem of Typology and Modifications - Stanyukovich-Denisova, Ekaterina Yu. (Actual Problems of Theory and History of Art, 2025)
Тhe author traces the development of typology and modifications of the exemplary houses in 1710-1760s Petersburg and comes to the conclusion that the policy of state regulation of the town building in the 18th c. resulted in forming the architecturally integral and functional city structure.
Keywords: exemplary building; St.Petersburg architecture; exemplary architectural projects; 18th century; modifications